2007
DOI: 10.1108/14637150710752335
|View full text |Cite
|
Sign up to set email alerts
|

Business process approach towards an inter‐organizational enterprise system

Abstract: PurposeTo review an existing enterprise resource planning (ERP) literature and provide the inter‐organizational practice of ERP system.Design/methodology/approachA focus group (FG) method was adopted as an exploratory means to gain insights and perspective of ERP systems.FindingsThe study suggests researchers re‐examine the following ERP issues at the inter‐organizational level, namely: selection of ERP packages, integration of business processes, knowledge and applications, implementation approaches, training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
3
19
0
1
Order By: Relevance
“…Moreover, our results are consistent with prior studies on the importance of a process view during IT implementation [12,35], and recent studies on RFID technology [1]. In fact, [35] observes the value of the process view, by stating that the main organizational issues, which may emerge during the implementation of IS projects, are better understood and managed as "they often enact as a set of critical factors in project dynamics, and ultimately lead to a project success or failure"( p. 434). Finally, the study confirms the capabilities of RFID technology as an enabler of transforming the existing picking and the shipping processes in real-world setting, which is consistent with prior studies on RFID technology [21,36].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our results are consistent with prior studies on the importance of a process view during IT implementation [12,35], and recent studies on RFID technology [1]. In fact, [35] observes the value of the process view, by stating that the main organizational issues, which may emerge during the implementation of IS projects, are better understood and managed as "they often enact as a set of critical factors in project dynamics, and ultimately lead to a project success or failure"( p. 434). Finally, the study confirms the capabilities of RFID technology as an enabler of transforming the existing picking and the shipping processes in real-world setting, which is consistent with prior studies on RFID technology [21,36].…”
Section: Resultssupporting
confidence: 92%
“…Like other networks technologies, the study shows the importance of increasing the positive RFID network externality effects by promoting the buy-in for wider RFID adoption and use among all TPL supply chain stakeholders [34]. Moreover, our results are consistent with prior studies on the importance of a process view during IT implementation [12,35], and recent studies on RFID technology [1]. In fact, [35] observes the value of the process view, by stating that the main organizational issues, which may emerge during the implementation of IS projects, are better understood and managed as "they often enact as a set of critical factors in project dynamics, and ultimately lead to a project success or failure"( p. 434).…”
Section: Resultssupporting
confidence: 89%
“…A factor that influenced this approach was previous experience of failed projects and the absence of a project management office (PMO) at Organisation A. Of particular interest is the unexpected finding that two of the large organisations (1 public and 1 private) engaged a "big bang" approach that has typically been associated in the literature with an approach better suited to small firms because of the high degree of risk involved (Vathanophas, 2007). This is in direct contrast to the approach taken by the other two firms where the managers openly insisted that the ITIL implementation "was not a project", but instead was viewed as implementation of continuous process improvement.…”
Section: Rq2: Are Public and Private Firms In The Us And Australia mentioning
confidence: 99%
“…In a recent study of how organizations implement business processes, Vathanophas (2007) noted that participants differed in their choice of implementation strategies. Some used the "big bang" approach (i.e., an implementation strategy that cuts over all parts of a system at the same time in a company or division), while others used phased or parallel approaches that bring on board new systems or processes module by module.…”
Section: Implementation Strategiesmentioning
confidence: 99%
“…These software systems are large, complex, and expensive, and also require a substantial amount of organizational change to implement, making them an ideal candidate for the use of BPM and cost modeling during the selection process [1]. Reference [1] identified several ERP process models that were used during the selection of an ERP system, including a number of themes that were different between processes at different organizations. The author's research indicated that the process of selection and implementation was highly individualized between organizations.…”
Section: Software Choicementioning
confidence: 99%